Thunbergia laurifolia leaf extract inhibits glutamate-induced neurotoxicity and cell death through mitophagy signaling - Wudtipong Vongthip (2022)
Oxidative stress plays a crucial role in neurodegeneration. Therefore, reducing oxidative stress in the brain is an important strategy to prevent neurodegenerative disorders. Thunbergia laurifolia (Rang-jued) is well known as an herbal tea in Thailand. Here, we aimed to determine the protective effects of T. laurifolia leaf extract (TLE) on glutamate-induced oxidative stress toxicity and mitophagy-mediated cell death in mouse hippocampal cells (HT-22). Our results reveal that TLE possesses a high level of bioactive antioxidants by LC–MS technique. We found that the pre-treatment of cells with TLE prevented glutamate-induced neuronal death in a concentration-dependent manner. TLE reduced the intracellular ROS and maintained the mitochondrial membrane potential caused by glutamate. Moreover, TLE upregulated the gene expression of antioxidant enzymes (SOD1, SOD2, CAT, and GPx). Interestingly, glutamate also induced the activation of the mitophagy process. However, TLE could reverse this activity by inhibiting autophagic protein (LC3B-II/LC3B-I) activation and increasing a specific mitochondrial protein (TOM20). Our results suggest that excessive glutamate can cause neuronal death through mitophagy-mediated cell death signaling in HT-22 cells. Our findings indicate that TLE protects cells from neuronal death by stimulating the endogenous antioxidant enzymes and inhibiting glutamate-induced oxidative toxicity via the mitophagy–autophagy pathway. TLE might have potential as an alternative or therapeutic approach in neurodegenerative diseases.